Density graded polymer composite foams. Issue 1 (January 2023) - Tan, XueMei; Rodrigue, Denis
This article reviews the main developments associated with density graded polymer composite foams. After a short introduction, a discussion is made on both density graded polymer-based composites and foams separately to better understand the challenges when both structures are combined together to produce composite foams. In all cases, the basic concepts, fabrication methods, main properties and general applications are presented. Opening for future works are also presented to conclude.